PROGRAM PIPANISASI DENGAN SISTEM ADMINISTRASI TERPADU AIR BERSIH DUSUN SONO TENGAH DESA KEBON AGUNG KABUPATEN MALANG - Dwi Purnomo; Wilyatin Agustina Bangun; Rokhyanto Rokhyanto (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P2M) IKIP Budi Utomo Malang, 2017)
Water is a primary requirement for humans, the process of obtaining it can be done in various ways, one of them is the underground water drilling process. The process of underground water drilling is also done in Sono Tengah. Because it is managed conventionally the water distribution process has not been maximized and in accordance with the expectations of all citizens. The results of initial observation at the drilling site is the need for clean water network arrangement and good administrative governance. Based on these two programs, the IbM program emphasizes the improvement of network and good administrative management system through the utilization of computerized system. Through the utilization of science and technology in the form of rearrangement of existing pipelines is expected to occur the distribution of water to every citizen well and all citizens in Sono Tengah can jointly enjoy the existence of well water drill. Therefore, based on the above fact, maintenance is required periodically and permanently for the continuity of the distribution of clean water. In this case IKIP Budi Utomo as one of the universities in Malang feel care and do one of the tri dharma that is devotion to society and results obtained are expected to be a good cooperation between the community and campus in the form of mutual assistance and coordinate between universities as the printing of scholars and the community as stakeholders.